Approaches to Dance (4): Moving, Teaching, Thinking, Writing: A Minor Excavation. (May 2022) - Whatley, Sarah
Abstract : This reflective essay traces a pathway through dance, beginning with the early influences in dance training and scholarship, through to building a University dance programme and research centre. With reference to the many scholars and artists who have been so important to this journey, the essay seeks to offer a glimpse into how a career in dance research often twists and turns through teaching, practice, writing and collaboration.